Analyses of the roles and potential targets of m7G-related genes in colorectal cancer using single-cell and bulk RNA sequencing data - Jie Hu; Zhihua Chen; Chenyang Ma; Yuan Fang; Quanfa Li; Jiebin Zheng; Jiannan He; Suyong Lin; Shaoqin Chen (PLoS ONE, 2025)
Background The pathogenesis of colorectal cancer is complex and difficult to treat, and there is a risk of metastasis and recurrence. m7G modification as a kind of RNA modification has been widely concerned in the field of tumor. However, there are few research in the field of CRC. This study aims to elucidate the effects of m7G modification on CRC from the perspective of single cell transcriptome and search for potential therapeutic targets. Methods We downloaded the single cell dataset using the GEO database and processed the data using the Seurat R package. gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) were used to analyze differential genes. CellChat is used for cell communication analysis. NMF differentiates subtypes. CIBERSORT and xcell are used to analyze immune cells. Lasso COX regression was used to search for hub genes. We explored the biological functions of NUDT10 utilizing biological experiments. Results Most m7G-related modification genes were significantly higher in expression in tumor tissues compared to normal tissues, primarily within epithelial cells. The DEGs of m7G-related genes expressed were mainly enriched in inflammation and metabolic pathways. NCBP2 and EIF3D could promote the occurrence and development of malignant epithelial tumor cells. In cellchat, m7G-related genes high group showed stronger interactions. m7G also affects tumor immune microenvironment and metabolism. In addition, seven genes were chosen for prognostic model construction. Biological experiments have demonstrated that NUDT10 promotes CRC progression. Conclusion This research revealed tumor growth and microenvironment changes mediated by m7G modification and constructed a prognostic model based on the hub genes, which will guide further exploration of m7G modification.